Political Routines in Press Translation - Kontos, Petros; Sidiropoulou, Maria (Meta, 2012)
The paper aims at showing that the journalist-translators’ decision-making with respect to what is to be included or left out of a target text, in the limited space provided by target newspapers, is governed by background knowledge considerations which reveal awareness of current political routines – in addition to generic constraints, narrative priorities, language-specific preference, etc. This is a pragmatic level of meaning which contributes to realizing the intention of the text producer. The paper examines two source text/target text pairs of articles on Tony Blair’s premiership, from The Guardian and The New York Times (2007), translated into Greek for Η Καθημερινή (I Kathimerini) broadsheet newspaper. It presents an overview of linguistic/cultural shifts which ensure acceptability in the target text, and shows that information selection/reduction adheres – inter alia – to political theoretical background knowledge: in this case, it assumes perception of the notion of political representation, which may vary across cultures, and awareness of the features of presidentialism according to Heywood, which parliamentary executives’ conduct often exhibits. Findings underline the multi-faceted task of journalist-translators and call for a multidisciplinary approach to news translation, which would encompass political theory perspectives, in addition to linguistic and journalistic perspectives to variation.